2006
DOI: 10.1197/j.aem.2006.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Disaster Preparedness in Los Angeles County

Abstract: Among hospitals in Los Angeles County, disaster preparedness and surge capacity appear to be limited by a failure to fully integrate interagency training and planning and a severely limited surge capacity, although there is a generally high level of availability of equipment and supplies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
89
3
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(103 citation statements)
references
References 24 publications
7
89
3
4
Order By: Relevance
“…Estimation of the potential increased demand in an emergency and considering areas for hospitalized patients in this situation are among the strengths of the hospitals. Identifying ways to increase hospital capacity at the time of disaster, considering vehicles and the resources required for transportation of patients in these conditions and identifying other locations with the possibility of converting them to patient care units such as hospital auditorium were the works done in this area which was consistent with Kaji et al study [16]. This study was conducted to evaluate the preparedness of Los Angeles Hospital.…”
Section: Discussionsupporting
confidence: 67%
“…Estimation of the potential increased demand in an emergency and considering areas for hospitalized patients in this situation are among the strengths of the hospitals. Identifying ways to increase hospital capacity at the time of disaster, considering vehicles and the resources required for transportation of patients in these conditions and identifying other locations with the possibility of converting them to patient care units such as hospital auditorium were the works done in this area which was consistent with Kaji et al study [16]. This study was conducted to evaluate the preparedness of Los Angeles Hospital.…”
Section: Discussionsupporting
confidence: 67%
“…reported that in Los Angeles hospitals, preparedness to disaster was low due to problems in planning and correct training. These findings are in line with our study [12]. In the study of Seyedin, evaluating the safety of 6 hospitals in Tehran, most of the studied hospitals had high safety level [13].…”
Section: Discussionsupporting
confidence: 81%
“…33 Prior investigations of academic ED leaders, 6,10,34 emergency health professionals, 9 hospital administrators, 35,36 infection prevention specialists, 37 and epidemiologists 38 document significant gaps, notably related to presence of general pandemic plans, 35 ED-specific plans, 9 pediatric-specific plans, 34 conduction of epidemic or pandemic simulations or drills, 6,8,9 plans for staffing and supply augmentation, 9,35 perceived pandemic readiness, 9,10,38 and coordination with public health agencies or other health care institutions. [35][36][37]39,40 Our findings parallel those in the existing literature but expand on prior work by contributing novel characterizations of preparedness from the pediatric EP leaders' perspective. Furthermore, in recognition of the vulnerability of the pediatric population during such an event, 33,[41][42][43][44][45] our study focused specifically on preparedness in pediatric institutions.…”
Section: Discussionsupporting
confidence: 79%